Evidence to Prevent Obesity: Focus on Diet, Physical Activity, and Behaviour Modifications - Karim, Norimah A.; Abd. Talib, Ruzita; Gan, Wan Ying; Syed Tarik Wafa, Sharifah Wajihah; Abdul Manaf, Zahara; Mohd Jamil, Sameeha; Abu Saad, Hazizi; Koh, Denise Choon Lian; Wong, Jyh Eiin; Mohd Elias, Siti Soraya; Mohamed Salleh, Razali; Pitil, Patricia Pawa; et al. (Malaysian Association for the Study of Obesity, 2024)
It is well acknowledged that unhealthy diet and physical inactivity are some of the contributing factors in the increasing prevalence of overweight and obesity. Since the last publication of the Strategies for the Prevention of Obesity (SPOM) in Malaysia (MASO, 2005) (Level 4), there have been numerous emerging evidence to further associate the role of diet and physical activity in the escalating prevalence of overweight and obesity in Malaysia. Studies have reported on the changes in food consumption patterns and dietary habits of Malaysians and the emergence of nutritional and health related problems in Malaysia. (IPH, 2017, Ahmad et al. 2019). In the Malaysia Lipid Study, Balasubramanian et al. (2020) (Level 3) identified four dietary patterns (DP) with distinct eating modes, namely home meal (HM), Chinese traditional (CT), plant foods (PF) and sugar-sweetened beverages (SSB). The study revealed that consumption of sugar-sweetened beverages (SSB) was notably linked to the highest risks for both BMI and waist circumference. Engaging in behaviors such as drinking coffee or tea with condensed milk (29%) or sugar (20.7%) and frequent eating out (12 ± 8 times per week) were also found to increase the likelihood of obesity (Balasubramanian et al., 2020) (Level 3). Engaging in physical activity holds a crucial role in preventing excess weight and obesity not only in kids and teenagers but also in adults, thus diminishing the likelihood of developing overweight or obesity in later life. Obesity is becoming a growing concern among individuals of all age groups, including children, on a global and local scale. Hence, there is a critical need for empirically based data to guide efforts in preventing and addressing obesity issues in Malaysia. Intervention programmes to address obesity problems require a multi-prong approach. This includes changes towards healthier dietary habits and increased physical activity. More importantly there needs to be a paradigm shift in the modification of behaviour to make these changes. This chapter discusses the dietary and physical activity evidence on how to manage obesity as well as behaviour modifications required to manage obesity. The conclusions will highlight some important evidence that can be utilized to propose strategies on obesity prevention in Malaysia.